Correction of anxiety as a fear factor in junior students of medical institutions of higher education (for example the Donetsk National Medical University) - Avetisova, I. S.; Potsulko О. А. (Вісник Донецького національного університету імені Василя Стуса. Серія Психологічні науки, 2023)
The study of the levels of personal and situational anxiety of junior medical students of the Donetsk National Medical University (Lyman, Ukraine), whose adaptation process has certain features determined by personal, social and economic and emotional factors are considered in this article. The essence of anxiety and its levels, rational and emotional approach, which was the basis of the proposed psychocorrective program to reduce anxiety levels in medical students are revealed. It has been proven that junior year students of medical institutions of higher education may experience stress due to regarding the high requirements for them as future doctors. The feeling of inner anxiety and tension in an uncertain and stressful situation can greatly interfere with them both during university studies and in the performance of professional duties. Therefore, it is important to correct the anxious state of medical students in order to eliminate in the future the appearance of professional fears due to constant anxiety in professional activities. It was found that the most influential factors in the development of a high level of anxiety in medical students of the 1st and 2nd years are frequent stress factors and significant tension during studies, which indicates the urgent need for psychological preparation of applicants to study at a medical university, and during the first years of study, conducting social-psychological trainings and psychocorrections such as positive inner speech and self-suggestion, fitback or art therapy. The practical recommendations for the formation of self-esteem by medical students based on successes both in personal life and at work are also provided in this article. It is worth stimulating the future doctor to address the question and fight with his own negative self-esteem and show him how to think from a scientific point of view, evaluate his behavior objectively and how to stop giving himself an assessment only in case of failure.